Overcoming the challenges of high‐energy X‐ray ptychography. (12th July 2019) - da Silva, Julio Cesar; Guilloud, Cyril; Hignette, Olivier; Jarnias, Christophe; Ponchut, Cyril; Ruat, Marie; Labiche, Jean-Claude; Pacureanu, Alexandra; Yang, Yang; Salome, Murielle; Bohic, Sylvain; Cloetens, Peter
Abstract : X‐ray ptychography was optimized at energies of 17 and 33.6 keV at the ESRF using Kirkpatrick–Baez mirrors. Abstract : X‐ray ptychography is a coherent diffraction imaging technique with a high resolving power and excellent quantitative capabilities. Although very popular in synchrotron facilities nowadays, its implementation with X‐ray energies above 15 keV is very rare due to the challenges imposed by the high energies. Here, the implementation of high‐energy X‐ray ptychography at 17 and 33.6 keV is demonstrated and solutions to overcome the important challenges are provided. Among the particular aspects addressed are the use of an efficient high‐energy detector, a long synchrotron beamline for the high degree of spatial coherence, a beam with 1% monochromaticity providing high flux, and efficient multilayer coated Kirkpatrick–Baez X‐ray optics to shape the beam. The constraints imposed by the large energy bandwidth are carefully analyzed, as well as the requirements to sample correctly the high‐energy diffraction patterns with small speckle size. In this context, optimized scanning trajectories allow the total acquisition time to be reduced by up to 35%. The paper explores these innovative solutions at the ID16A nano‐imaging beamline by ptychographic imaging of a 200 nm‐thick gold lithography sample.